Water footprint for Korean rice products and virtual water trade in a water-energy-food nexus. Issue 6 (18th August 2018) - Lee, Sang-Hyun; Choi, Jin-Yong; Yoo, Seung-Hwan; Mohtar, Rabi H.
ABSTRACT: One possible approach for addressing water and food insecurity involves food production, trade, and water used elsewhere. In this study, we introduce a water footprint for Korean rice products and focus on the impacts of localized cultivation and water supply systems on the water footprint. In addition, we discuss several studies on the application of water footprint and virtual water trade in water and food management in Korea. Finally, we suggest the role of water footprint and virtual water trade in sustainable resource management through a water-energy-food nexus approach.